1997
DOI: 10.1099/0022-1317-78-2-401
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AP1 during cellular differentiation determines human papillomavirus E6/E7 expression in stratified epithelial cells.

Abstract: E6 and E7 oncoproteins of human papillomavirus (HPV) play significant roles in the pathogenesis of cervical cancer. However, the pattern of E6/E7 expression during the productive virus life cycle in differentiating epithelia of the uterine cervix remains unclear. In addition, little is known about the cellular factors regulating E6/E7 expression in differentiating epithelia. In the present study, using transient expression assays and DNA binding assays, we demonstrated that E6/E7 transcription is critically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…The hypothesized chromatin-binding corepressor (Hou et al 2000) is now identified as Brd4. Second, the identification of AP-1, but not Sp1 and YY1 (data not shown), as a critical cellular transcription factor able to initiate transcription in vitro from silenced HPV chromatin, whose structure was first observed nearly 30 years ago by electron microscopy with viral samples obtained from human plantar warts (Favre et al 1977), directly demonstrates the involvement of AP-1 in HPV transcription and is consistent with genetic studies indicating the importance of AP-1-binding sites for E6/E7 gene expression in both differentiated and undifferentiated cell types, including keratinocytes and stratified epithelial tissues (Kyo et al 1997;Zhao et al 1997;and references therein). Third, the finding that acetylation on histones H3 and H4 remains unaltered following Brd4-mediated recruitment of E2 to the E6 promoter region indicates that acetylation on histone tails may also signal the recruitment of a sequence-specific transcriptional repressor whose chromatin targeting activity depends on the binding of a corepressor to acetylated chromatin.…”
Section: Discussionsupporting
confidence: 58%
“…The hypothesized chromatin-binding corepressor (Hou et al 2000) is now identified as Brd4. Second, the identification of AP-1, but not Sp1 and YY1 (data not shown), as a critical cellular transcription factor able to initiate transcription in vitro from silenced HPV chromatin, whose structure was first observed nearly 30 years ago by electron microscopy with viral samples obtained from human plantar warts (Favre et al 1977), directly demonstrates the involvement of AP-1 in HPV transcription and is consistent with genetic studies indicating the importance of AP-1-binding sites for E6/E7 gene expression in both differentiated and undifferentiated cell types, including keratinocytes and stratified epithelial tissues (Kyo et al 1997;Zhao et al 1997;and references therein). Third, the finding that acetylation on histones H3 and H4 remains unaltered following Brd4-mediated recruitment of E2 to the E6 promoter region indicates that acetylation on histone tails may also signal the recruitment of a sequence-specific transcriptional repressor whose chromatin targeting activity depends on the binding of a corepressor to acetylated chromatin.…”
Section: Discussionsupporting
confidence: 58%
“…pGL3-EREpromoter was constructed by inserting head-in-tail tetramers of the ERE located at Ϫ2677 in the hTERT promoter, into the enhancer-less vector pGL3-promoter (18). pGL2-HPV31URR-luc vector is an HPV-31 enhancer and promoter-luciferase reporter containing the whole upstream regulatory region (URR) of HPV-31 cloned upstream of the luciferase gene in pGL2-Basic (27). These reporter plasmids were transiently transfected into cells for 24 h using LipofectAMINE Plus (Invitrogen) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Whether the virus reactivates S phase in a terminally differentiated, postmitotic cell or keeps active the cell cycle of a differentiating cell is unclear. Indeed, the phenomenon is variably described as S phase reentry in postmitotic, differentiated cells (Jian et al, 1998;Chien et al, 2002), maintenance of cells in a proliferative state in the course of differentiation (Kyo et al, 1997;Nguyen et al, 2002) or, perhaps most appropriately, left undecided (Jones et al, 1997).…”
Section: Introductionmentioning
confidence: 99%